Retaining Generation Z Talents in The Hospitality Industry: A Systematic Review and Framework for Bali's Tourism Workforce Development (International Journal of Applied Research and Innovation, 2026)
This study aims to identify the factors influencing Generation Z talent retention in the hospitality industry and to develop a contextualized retention framework for Bali's tourism workforce. A Systematic Literature Review (SLR) was conducted following the PRISMA guidelines, resulting in the inclusion of 31 peer-reviewed journal articles for qualitative synthesis. The findings indicate that Generation Z retention is determined by three interrelated dimensions: intrinsic factors, including meaningful work, work-life balance, and psychological well-being; extrinsic factors, comprising transparent career pathways, fair compensation, collaborative leadership, and inclusive organizational culture; and contextual factors rooted in local cultural values. The review also identifies effective retention strategies, including digital recruitment, structured onboarding, flexible work arrangements, continuous competency development, and holistic well-being initiatives. By contextualizing global evidence within Bali's tourism environment, this study proposes a three-pillar retention framework integrating intrinsic, extrinsic, and contextual dimensions, with Tri Hita Karana and gotong royong serving as key cultural foundations. The proposed framework contributes to hospitality human resource management by providing practical guidance for developing a sustainable and culturally responsive tourism workforce.